Outward FDI of Malaysia: An Empirical Examination from Macroeconomic Perspective - Jerome, Kueh; Puah, Chin-Hong; Albert, Apoi (2008)
Outward FDI of Malaysia was nearly non-existent prior to 1970s. Nonetheless, recently Malaysia has not only been able to sustain FDI inflows position, but also emerged as the fifth largest investor among the developing economies in Asia region (UNTACD, 2005). This study aims to investigate the selected macroeconomic determinants of outward FDI of Malaysia, namely income, exchange rate and openness. The Johansen and Juselius cointegration test and the vector error correction model are applied in this study to analyze the quarterly data from 1991:Q1 to 2004:Q4. The findings verified that the outward FDI of Malaysia is determined by income, exchange rate and openness of the economy in both the short-and long-run.